ICT and the classroom: from the transmission to sharing and from performance to interaction - Gouveia, Luis Borges (2021)
We have completed the second decade of the new millennium. Furthermore, we have experienced a pandemic and the accelerating effect it has had on the use of digital and basic distance learning mechanisms. The changes caused by digital, by the intensive use of individual mediation forms, such as those made possible by digital devices, have made the tension towards traditional teaching and learning environments even more intense. Thus, the classroom space has become small: insufficient for society's needs, tiny for those who teach, and insignificant for those who learn. Digital has brought new forms of time and space that we need to explore and greater urgency in dealing with the group and cooperation between individuals as basic dimensions to prepare for a reality where creativity and innovation are required values. A brief reflection on the scope and possibility of technologies is proposed here to serve teaching and learning space more aligned with our time's needs, taking the classroom as a starting point.